A Study to Assess the Effectiveness of Planned Teaching Program on Knowledge and Practice of Labour Care Guide During Labour Among Nursing Students Posted in Labour Room at Sgt Hospital, Gurugram - Sharma, Nitika; Singh, Shivani.; Jyoti, Gyan; Singh, Pooja; Harshlata, Harshlata (Journal of Neonatal Surgery, 2025)
The aim of the study was to assess the knowledge of labour care guide during labour among nursing students posted in labour room before teaching is administered. To identify the practice of labour care guide during labour among nursing students posted in labour room before teaching is administered To assess the knowledge regarding labour care guide among nursing students posted in labour room after the teaching is administered. To identify the practice regarding labour care guide among nursing students posted in labour room after teaching is administered. The aim of the study to the effectiveness of planned teaching program on knowledge and practice of labour care guide among nursing students posted in labour room. To associate demographic variables with knowledge and practices of labour care guide among nursing students posted in labour room was to study the effectiveness of planned teaching program on knowledge and practice of labour care guide among nursing students posted in labour room. A pre-experimental study was conducted from month of April 2023 to September 2023 among 60 Nursing students posted in labour room at SGT Hospital, Gurugram after obtaining informed consent. The finding of the study revealed that in pre-test knowledge- 31.7% had inadequate, 68.3% had moderate knowledge and pre-test practice 16.7% had poor and 83.3% had average practice regarding labour care guide among nursing students. Post-test knowledge 86.7% had adequate and 13.3% had moderate knowledge. Post-test practice 91.7% had good practice and 8.3% had average practice regarding labour care guide. Knowledge was significantly associated with educational qualification 0.042 and previous experience in hospital 0.038 significantly associated at p<0.05 level. Practice was significantly associated with the previous experience in hospital 0.047 significantly associated at p<0.05 level. Planned teaching programme will be effective in improving knowledge and practice regarding labour care guide among nursing students posted in labour room in SGT Hospital, Gurugram